Occupational Health, Safety and Extreme Poverty: A Qualitative Perspective from Bangladesh - Owasim Akram (Occupational Health and Safety Society of Nepal, 2015)
Poor occupational health and safety damages many lives and livelihoods which impedes economic growth. Poor and unsafe work conditions are both a cause and consequence of extreme poverty. Both reinforce each other negatively. The significance of occupational health and safety is particularly strong in countries like Bangladesh where it is not addressed or explored much. This study focuses on urban and peri-urban Bangladesh drawing from: 15 Life History (LH) interviews with people who became disabled during work, 10 in-depth interviews with vulnerable workers in high risk environments; and key informant interviews (KII) with five senior management officials in high risk workplaces. Other studies have also been consulted on occupation safety in rural and urban Bangladesh. Findings confirm that extreme poor people are not only disproportionately drawn into high risk and unhealthy jobs but also the accidents and health problems that arise from these jobs exacerbate poverty. Employers were found to be reluctant to take responsibility for workers and any support offered to injured workers was mainly done out of charity. Sub-contracting was found to be potentially harmful practice of the business/industry owners which makes workers more vulnerable. The paper concludes that occupational health and safety in Bangladesh should be a higher priority in discussions of extreme poverty, its consequences and its solutions. DOI: http://dx.doi.org/10.3126/ijosh.v4i1.10654